The Use of Action Songs on Young Learners’ Pronunciation Accuracy - Muhammad Farhan (Lingedu: Journal of Linguistics and Education, 2026)
This study aims to know how action songs are used to help elementary school students improve their English pronunciation in one of schools in Aceh. The study focuses on the problem that many students still have difficulty with English sounds, word stress, and rhythm, which makes it hard for them to speak clearly and confidently. The study employed a descriptive qualitative method. Data were collected from classroom observation and interviews with several students. The results show that action songs help students in many ways. Rhythm helps them say English words with correct stress and beats. Word repetition helps them remember sounds and improve pronunciation. Movements keep students active, reduce boredom, and help them connect sounds with meaning. Students with different ability levels showed improvement in pronunciation, confidence, and participation in class activities. This research concludes that action songs are a fun and useful technique for pronunciation practice for children, especially in classes with limited learning resources.